MAKNA NAMA-NAMA MAHASISWA SASINDO UNPAM (TINJAUAN ANTROPOLINGUISTIK) - Bram Denafri; Ratna Juwitasari Emha (Prodi Sastra Indonesia Universitas Pamulang, 2022)
Pamulang University students come from various cultural backgrounds, such as Javanese, Sundanese, Batak, Minang, Acehnese, Palembang, East Nusa Tenggara, Bugis, Dayak, Balinese and Papuan cultures. The diversity of Pamulang University students is of course also reflected in the names of these students. The name will reflect the student's cultural identity. Therefore, the purpose of this study was to describe the meaning of the names of Sasindo Unpam students. This type of research is descriptive research because this study describes the meaning of the names of Sasindo Unpam students. This research approach is a qualitative approach because the data in this study are qualitative data, namely the names of Sasindo Unpam students. Furthermore, a quantitative approach was used to determine the percentage ratio of the meanings of the names of Sasindo Unpam students based on categories. The data sources in this study were students of Sasindo Unpam. The results of this study found that the meaning of the names of Sasindo Unpam students based on time as many as 16 data, clans 10 data, Character names 12 data, Abbreviations 3 data, writing errors 2 data, Regional language 11 data, Hope 5 data, Foreign language 28 data, Object name 2 data, Child order 6 data.Keywords: anthropolinguistics, meaning, students